Instructor Priorities for Undergraduate Organic Agriculture Education. Issue 1 (1st September 2019) - Jabbour, Randa; Pellissier, Makenzie E.
Abstract : Core Ideas: Instructors' priorities include soil fertility, ecology, and certification standards. Instructors consider systems thinking and nutrient management to be the most challenging areas for students to learn. The lack of teaching materials specific to organic agriculture highlights an opportunity for textbook development in this area. Organic agriculture courses and degrees in higher education have become more common in recent decades. In this article, we characterized instructor priorities for organic agriculture education and identified critical concepts and skills to be included in curriculum. We used interviews and surveys to learn from 19 instructors from universities and colleges in the United States. Interviews were recorded, transcribed, and coded for frequency of mentions. The critical concepts most frequently mentioned by instructors were soils, ecological principles, and certification standards. The topics that instructors most frequently mentioned covering occasionally or not at all included social dimensions, climate change, and livestock production. Instructors frequently mentioned the challenges of lack of teaching materials specific to organic agriculture and lack of expertise, given the multidisciplinary span of organic agriculture. Including guest lectures was mentioned as a way to cover topics where instructors felt they had less knowledge or expertise. Instructors stated that the most challenging topics and skills for students to learn included systems thinking, managing nutrients, and performing fertilizer calculations. Our summary highlights the specific concepts that instructors across the United States prioritize in their teaching, laying the groundwork for future curriculum development. They offer valuable insight into the challenges and successes in organic agriculture teaching.